Reconstructing Nitrogen Sources to Earth’s Earliest Biosphere at 3.7 Ga - Stüeken, Eva E.; Boocock, Toby; Szilas, Kristoffer; Mikhail, Sami; Gardiner, Nicholas J. (Frontiers in Earth Science, 2021)
Earth’s sedimentary record has preserved evidence of life in rocks of low metamorphic grade back to about 3.2-3.5 billion years ago (Ga). These lines of evidence include information about specific biological metabolisms, permitting the reconstruction of global biogeochemical cycles in the early Archean. Prior to 3.5 Ga, the geological record is severely compromised by pervasive physical and chemical alteration, such as amphibolite-granulite facies metamorphic overprinting. Despite this alteration, evidence of biogenic organic matter is preserved in rare localities, including meta-turbidites from the 3.8-3.7 Ga Isua Supracrustal Belt, Western Greenland. But detailed insights into metabolic strategies and nutrient sources during the time of deposition of these Eoarchean meta-sedimentary rocks are lacking. Here we revisit the Isua meta-turbidites and provide new data for metal abundances as well as organic carbon and nitrogen isotope values. Our results reveal mixing between authigenic and detrital nitrogen phases with the authigenic phase likely fractionated by metamorphic degassing. Rayleigh fractionation models of these 3.7 Ga samples indicate pre-metamorphic δ15N values of between -1‰ to -10‰. The most plausible initial values are below -5‰, in agreement with a prior study. While the upper endmember of -1‰ could indicate biological N2 fixation at 3.7 Ga, the more plausible lighter values may point towards a distinct biogeochemical nitrogen cycle at that time, relative to the rest of Earth’s history. In light of recent experimental and phylogenetic data aligned with observations from the modern atmosphere, we tentatively conclude that lightning and/or high-energy photochemical reactions in the early atmosphere may have contributed isotopically light nitrogen to surface environment(s) preserved in the Isua turbidites. In this case, recycling of Eoarchean sediments may have led to the isotopically light composition of the Earth’s upper mantle dating back to at least 3.2 Ga.